Novel Au–SiO2–WO3 Core–Shell Composite Nanoparticles for Surface‐Enhanced Raman Spectroscopy with Potential Application in Cancer Cell Imaging. (9th September 2019) - Martinez Pancorbo, Pablo; Thummavichai, Kunyapat; Clark, Louise; Tabish, Tanveer A.; Mansfield, Jessica; Gardner, Ben; Chang, Hong; Stone, Nick; Zhu, Yanqiu
Abstract: With the rapid development of nanotechnology during the last decades, the ability to detect and control individual objects at the nanoscale has enabled us to deal with complex biomedical challenges. In cancer imaging, novel nanoparticles (NPs) offer promising potential to identify single cancer cells and precisely label larger areas of cancer tissues. Herein, a new class of size tunable core–shell composite (Au–SiO2 –WO3 ) nanoparticles is reported. These nanoparticles display an easily improvable ≈10 3 surface‐enhanced Raman scattering (SERS) enhancement factor with a double Au shell for dried samples over Si wafers and several orders of magnitude for liquid samples. WO3 core nanoparticles measuring 20–50 nm in diameter are sheathed by an intermediate 10–60 nm silica layer, produced by following the Stöber‐based process and Turkevich method, followed by a 5–20 nm thick Au outer shell. By attaching 4‐mercaptobenzoic acid (4‐MBA) molecules as Raman reporters to the Au, high‐resolution Raman maps that pinpoint the nanoparticles' location are obtained. The preliminary results confirm their advantageous SERS properties for single‐molecule detection, significant cell viability after 24 h and in vitro cell imaging using coherent anti‐stokes Raman scattering. The long‐term objective is to measure SERS nanoparticles in vivo using near‐infrared light. Abstract : A novel core–shell composite nanoparticle design for surface‐enhancement Raman spectroscopy (SERS) imaging with potential cancer cells imaging and detection applications is fabricated following modified versions of the Turkevich method and Stober process. The gold external shell plasmons are activated by near‐infrared lasers, which enhance the 4‐mercaptobenzoic acid molecules vibrational modes. SERS enhancement factor for double gold shells reaches 8 × 10 2 .